Glycogenic Hepatopathy in Type 1 Diabetes Mellitus - Murat Atmaca; Rifki Ucler; Mehmet Kartal; Ismet Seven; Murat Alay; Irfan Bayram; Sehmus Olmez (Case Reports in Hepatology)
Glycogenic hepatopathy is a rare cause of high transaminase levels in type 1 diabetes mellitus. This condition, characterized by elevated liver enzymes and hepatomegaly, is caused by irreversible and excessive accumulation of glycogen in hepatocytes. This is a case report on a 19-year-old male case, diagnosed with glycogenic hepatopathy. After the diagnosis was documented by liver biopsy, the case was put on glycemic control which led to significant decline in hepatomegaly and liver enzymes. It was emphasized that, in type 1 diabetes mellitus cases, hepatopathy should also be considered in the differential diagnoses of elevated liver enzyme and hepatomegaly.